2013
DOI: 10.1186/1471-2407-13-457
|View full text |Cite
|
Sign up to set email alerts
|

Germline variants in MRE11/RAD50/NBN complex genes in childhood leukemia

Abstract: BackgroundThe MRE11, RAD50, and NBN genes encode proteins of the MRE11-RAD50-NBN (MRN) complex involved in cellular response to DNA damage and the maintenance of genome stability. In our previous study we showed that the germline p.I171V mutation in NBN may be considered as a risk factor in the development of childhood acute lymphoblastic leukemia (ALL) and some specific haplotypes of that gene may be associated with childhood leukemia. These findings raise important questions about the role of mutations in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Similar results were reported in our current and previous study among non-selected breast cancer patients [11]. In our another study we confirmed the association of the variant allele of the RAD50 rs171660505 with decreased risk of the childhood acute lymphoblastic leukemia [18]. A. Choudhury and colleagues have genotyped SNPs in DSB signalling genes and found an marginally association of the MRE11 3′UTR SNP rs2155209 with bladder cancer [17].…”
Section: Discussionsupporting
confidence: 90%
“…Similar results were reported in our current and previous study among non-selected breast cancer patients [11]. In our another study we confirmed the association of the variant allele of the RAD50 rs171660505 with decreased risk of the childhood acute lymphoblastic leukemia [18]. A. Choudhury and colleagues have genotyped SNPs in DSB signalling genes and found an marginally association of the MRE11 3′UTR SNP rs2155209 with bladder cancer [17].…”
Section: Discussionsupporting
confidence: 90%
“…A higher frequency of occurrence of the heterozygous c.657del5 mutation has been observed in patients with melanoma and non-Hodgkin lymphoma (22). However, other studies have reported that c.657del5 did not occur more frequently in breast (9,22), colorectal (22) and larynx cancer (13), which suggests that this variant is not a risk factor for these malignancies. Similarly, in the present study, no association between the occurrence of the c.657del5 mutation and the risk of developing lung cancer was observed.…”
Section: Discussionmentioning
confidence: 92%
“…The occurrence of the p.I171V variant in the NBN gene has been previously linked with elevated risk of several types of cancer. A significantly higher frequency of the p.I171V variant was observed in ALL, breast, larynx and colorectal cancer, and in multiple primary tumors of the head and neck (9,13,15). However, such an association was not observed for solid malignancies in children (11).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations